Myeloperoxidase-induced genomic DNA-centered radicals - Gomez-Mejiba, Sandra Esther (2010)
Myeloperoxidase (MPO) released by activated neutrophils can initiate and promote carcinogenesis. MPO produces hypochlorous acid (HOCl) that oxidizes the genomic DNA in inflammatory cells as well as in surrounding epithelial cells. DNA-centered radicals are early intermediates formed during DNA oxidation. Once formed, DNA-centered radicals decay by mechanisms that are not completely understood, producing a number of oxidation products that are studied as markers of DNA oxidation. In this study we employed the 5,5-dimethyl-1-pyrroline N-oxide-based immuno-spin trapping technique to investigate the MPO-triggered formation of DNA-centered radicals in inflammatory and epithelial cells and to test whether resveratrol blocks HOCl-induced DNA-centered radical formation in these cells. We found that HOCl added exogenously or generated intracellularly by MPO that has been taken up by the cell or by MPO newly synthesized produces DNA-centered radicals inside cells. We also found that resveratrol passed across cell membranes and scavenged HOCl before it reacted with the genomic DNA, thus blocking DNA-centered radical formation. Taken together our results indicate that the formation of DNA-centered radicals by intracellular MPO may be a useful point of therapeutic intervention in inflammation-induced carcinogenesis.